250 delicious recipes plus techniques and tips from the Culinary Institute of America (New York, 2001)
Weight Watchers has teamed up with The Culinary Institute of America–the country’s premier cooking school–to create this irresistible collection of recipes for fresh, creative dishes that are packed with flavor, not calories. Accompanied by more than 60 tantalizing color photographs, the 250 accessible recipes offer delicious options for every part of the menu, from a satisfying Penne with Creamy Garlic-Parmesan Sauce entrée to a simple-but-spectacular Berry Napoleon dessert. Every recipe includes nutritional information and POINTS® values from the Weight Watchers Winning Points® Weight Loss Plan, making it easy to maintain a healthy diet. Throughout, the chefs of The Culinary Institute of America share expert tips on shopping and meal preparation, including clever techniques like dry-searing meats, working pizza dough, and more.
Keywords: Reducing diets,Ăn kiêng; Recipes,Công thức nấu ăn